Interfacial Architectures Derived by Lithium Difluoro(bisoxalato) Phosphate for Lithium‐Rich Cathodes with Superior Cycling Stability and Rate Capability. Issue 1 (20th December 2016) - Han, Jung‐Gu; Park, Inbok; Cha, Jiho; Park, Suhyeon; Park, Sewon; Myeong, Seungjun; Cho, Woograe; Kim, Sung‐Soo; Hong, Sung You; Cho, Jaephil; Choi, Nam‐Soon
Abstract: The front cover artwork is provided by the group of Nam‐Soon Choi at Ulsan National Institution Science Technology, Republic of Korea. The image shows lithium difluoro(bisoxalato) phosphate as an oxidizable additive for in‐situ formation of a stable artificial solid electrolyte interphase layer on the Li‐rich cathode. Read the full text of the Article at10.1002/celc.201600297 . Abstract : "A lithium difluoro(bisoxalato)phosphate‐derived solid electrolyte interphase layer effectively suppresses unwanted electrolyte decomposition at high voltages and mitigates the voltage decay of lithium‐rich cathodes caused by phase transformation to spinel‐like phases during cycling…" Find out more about the story behind the front cover research at10.1002/celc.201600297 .